New labour laws and policy, 1972; containing Labour laws (amendment) ord., 1972; Employees' old age pension ord., 1972; Workers' children (education) ord., 1972; Text of new labour policy (1972); Arbitration of labour disputes order, 1972 - Chaudhary, Muhammad Anwar (Lahore Law Times Publications, 1972)
Commentary.